PENTINGNYA PERSIAPAN DANA PENSIUN UNTUK MASA DEPAN - YULFISWANDI YULFISWANDI; CALVIN CALVIN; IVAN JONES; RICKO MARTHIN; VALENCIA VALENCIA; VINNA RUDIANTO (Universitas Mahasaraswati K. Mataram, 2023)
Pension funds are a form of financial management that is important to carry out in preparation for the future. Retirement planning can be considered as an investment to deal with unexpected financial risks in retirement, such as high medical expenses and daily living needs. The number of pension fund participants has increased which shows that public awareness of the importance of preparing pension funds is increasing. Companies can also provide support to increase employee awareness in setting up a pension fund. Planned pension funds can provide life welfare guarantees in retirement and can be used for various purposes, such as covering the necessities of life or running a business. Therefore, planning for retirement funds is very important for every individual to prepare for the future